Systematic program design : from clarity to efficiency - Liu, Yanhong Annie, 1965- (Cambridge University Press, 2013)
"A systematic program design method can help developers ensure the correctness and performance of programs while minimizing the development cost. This book describes a method that starts with a clear specification of a computation and derives an efficient implementation by step-wise program analysis and transformations. The method applies to problems specified in imperative, database, functional, logic, and object-oriented programming languages with different data, control, and module abstractions. Designed for courses or self-study, this book includes numerous exercises and examples that require minimal computer science background, making it accessible to novices. Experienced practitioners and researchers will appreciate the detailed examples in a wide range of application areas including hardware design, image processing, access control, query optimization, and program analysis. The last section of the book points out directions for future studies"--